Stabilization, safety, and security of distributed systems : 21st International Symposium, SSS 2019, Pisa, Italy, October 22-25, 2019, Proceedings /: 21st International Symposium, SSS 2019, Pisa, Italy, October 22-25, 2019, Proceedings. (2019) - Unknown
No abstract available